FRI0008 IGM ANTIBODIES AGAINST MALONDIALDEHYDE AND PHOSPHORYLCHOLINE IN DIFFERENT SYSTEMIC RHEUMATIC DISEASES. (2nd June 2020) - Thiagarajan, D.; Lundström, S.; Zubarev, R.; Sun, J.; Alarcon-Riquelme, M.; Frostegård, J.
Abstract : Background: IgM antibodies against phosphorylcholine (anti-PC) and malondialdehyde (anti-MDA) may have protective properties in both atherosclerosis and rheumatic disease, especially anti-PC. Low levels of IgM anti-PC is associated with SLE itself and also with atherosclerotic plaques 1 and with being a non-responder to biologics in RA. 1 We determined mechanisms by which anti-PC (and to some extent anti-MDA) could be protective: 1: anti-inflammatory; 2: inhibition of uptake of oxLDL in macrophages, 3: inhibition of cell death. 1 4: increase in clearance of human dead cells, 2 5: anti-PC promotes polarization of T regulatory cells in SLE-patients´ T cells from a low level and also in cells from atherosclerotic plaques. 3 Objectives: To compare systemic rheumatic diseases in relation to natural anti-PC and anti-MDA, to develop novel classifications but also potential treatment against rheumatic disease. We here determine anti-PC and anti-MDA in different systemic rheumatic conditions and study there potential role properties. Methods: Anti-PC and anti-MDA was measured using ELISA in patients with SLE (374), RA (354), Mixed connective tissue disease (MCTD, 77), Systemic sclerosis (SSc, 331), Sjögren's syndrome (SjS, 324), primary antiphospholipid syndrome (PAPs, 65), undifferentiated connective tissue disease (UCTD, 118) and 515 matched healthy controls (HC). Cardiovascular score (CV) was broadly defined based on clinical disease symptoms. Anti-PC and anti-MDA peptide/protein characterization were compared using a proteomics de novo sequencing approach. anti-MDA and anti-PC were extracted from total IgM. The proportion of Treg cells was determined by flow cytometry. Results: The maximal difference between cases and controls was shown for MCTD: significantly lower IgM Anti-PC but not anti-MDA among patients (median 49.3RU/ml vs 70.4 in healthy controls, p(t-test)=0.0037). IgM low levels were more prevalent in MCTD, SLE, SjS, SSc and UCTD. IgM anti-PC variable region profiles were different from and more homologous than anti-MDA. Anti-PC but not anti-MDA were significantly negatively correlated with CV in the whole patient group. In contrast to IgM anti-PC, anti-MDA did not promote polarization of Tregs. Conclusion: Anti-PC is decreased in MCTD and also in SLE, SjS and SSc but not in other studied diseases. Anti-PC may thus differentiate between these. In contrast, anti-MDA did not show these differences between diseases studied. Anti-PC level is negatively correlated with CV in the patient group cohort. In contrast to anti-PC, anti-MDA did not promote Treg polarization. These findings could have both diagnostic and therapeutic implications, one possibility being active or passive immunization with PC in some rheumatic conditions. References: [1]Frostegard J. Immunity, atherosclerosis and cardiovascular disease. BMC Med . 2013;11:117. [2]Rahman M, Sing S, Golabkesh Z, Fiskesund R, Gustafsson T, Jogestrand T, Frostegard AG, Hafstrom I, Liu A and Frostegard J. IgM antibodies against malondialdehyde and phosphorylcholine are together strong protection markers for atherosclerosis in systemic lupus erythematosus: Regulation and underlying mechanisms. Clin Immunol . 2016;166-167:27-37. [3]Sun J, Lundstrom SL, Zhang B, Zubarev RA, Steuer J, Gillgren P, Rahman M, Ajeganova S, Liu A and Frostegard J. IgM antibodies against phosphorylcholine promote polarization of T regulatory cells from patients with atherosclerotic plaques, systemic lupus erythematosus and healthy donors. Atherosclerosis . 2018;268:36-48. Acknowledgments: Preciseads Clinical Consortium Disclosure of Interests: Divya Thiagarajan: None declared, Susanna Lundström: None declared, Roman Zubarev: None declared, jitong Sun: None declared, Marta Alarcon-Riquelme: None declared, Johan Frostegård Grant/research support from: Unconditional competitive grant from Amgen, related only to PCSK9, not the topic of this abstract